Chemical Constituents and Biological Activity of Four Melicope Species (Rutaceace) - Mohd Hashim, Najihah (2005)
Four Melicope species from Rutaceae family were phytochemically studied and screened for their biological activities. These species, Melicope lunu-ankenda (Gaertn.) T.G. Hartley, Melicope latifolia @.C) T.G. Hartley, Melicope clemensiae (Men.) Liu and Melicope confisa T.G. Hartley were collected from Sandakan, Sabah. The chemical studies on the leaves and stem bark of these species involves extraction using three organic solvents of different polarity and isolation of compounds by using several chromatographic techniques including vacuum liquid chromatography and gravity column chromatography. The structural elucidation of the isolated compounds was carried out using spectroscopic methods, UV, IR, NMR, MS and also by comparison with the literature data. These techniques have led to the isolation and identification of several compounds of different classes, furoquinoline alkaloids, flavanoid, lignan, cinnamic acid derivative and sterols. The crude extracts and isolated compounds were screened for antimicrobial, antioxidant and cytotoxic activities using disc diffusion method, DPPH (1,l-Diphenyl-Zpircrylhydrazyl) and MTT (Microculture Tetrazoliurn Salt) assays, respectively. The microbes used for antimicrobial tests were methicillin resistant S. aureus (MRSA), B. subtilis, P. aeruginosa, S. typhimurium, C. albicans, A. ochraceaus and S. cerevisiae. Detail study on the leaves of Melicope lunu-ankenda afforded 7-geranyloxycinnamic acid (90) and sesarnin (91). Sesamin (91), a lignan was also found from the stem bark of the same plant together with pacyhpodol (13), a flavanoid. Chemical investigations on the leaves of Melicope latifolia have resulted in the isolation of two alkaloids, dictamnine (24) and confusameline (7). Isolation work on the leaves of Melicope clemensiae gave two compounds, sesarnin (91) and P-sitosterol (92). The latter compound, a sterol was also found to be the constituent of the stem bark of the species. Ecdysterone (94), stigmasterol (93) and p-sitosterol (92) were isolated from the leaves of Melicope confusa, whereas from the stem bark, ecdysterone (94) and P-sitosterol(92) were isolated. The leaf extracts of Melicope clemensiae possesses strong antimicrobial activity against MRSA (Methicillin resistant Staphylococcus aureus) whereas its stem bark extracts exhibited moderate activity against the same bacteria. Moderate activity was observed in both leaves and stem bark extracts of this species, towards targeted fungi. The methanol bark extract of Melicope confusa also showed moderate activity against Pseudomonas aeruginosa and Candida albicans. Other crude extracts and isolated compounds, 7-geranyloxycinnamic acid (90) and sesamin (91) showed weak inhibition on the growth of the organisms. Crude extracts of Melicope lunu-ankenda, Melicope latifolia and Melicope clemensiae exhibited free radical scavenging activity towards DPPH but no activity was observed in the crude extracts of Melicope conjksa. As for the cytotoxic activity, all the crude extracts of Melicope confisa and Melicope clemensiae were not cytotoxic towards the HL 60 cells line. Meanwhile, strong cytotoxic activity was exhibited in chloroform and petroleum ether extracts of the leaves of M lunuankenda and M clemensiae, respectively. Both isolated compounds, 7-geranyloxycinnamic acid (90) and sesamin (91) showed weak activity as antimicrobes and as free radical scavengers. Although dictamnine (24) shows a weak free radical scavenger, it possesses a moderate antimicrobial activity against some of the microbes. Confusameline (7) however, shows a moderate free radical scavenging activity. Cytotoxic activities were also tested on 7- geranyloxycinnamic acid (90), sesamin (91) and dictarnnine (24). 7- Geranyloxycinnamic acid (90) exhibited a weak cytotoxic activity against HL 60 cells whereas sesamin (91) and dictamnine (24) show moderate activity towards the cells.